Does an Authoritative Parenting Style Associate with Secure Attachment to Father? - Fatmawati, Fatmawati; Maryam, Siti (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Good parenting produces a good mutual relationship between parent and child. Fathers have a role in parenting. A father is involved in nurturing by interacting with children and utilizing his resources, including physical, cognition, and affection. To that end, this study aimed to investigate the relationship between authoritative parenting and secure attachment to fathers among adolescents in Pidie-Aceh, Indonesia. This study used a purposive sampling technique with a total sample of 200 teenagers. Data collection techniques were performed by using an authoritative parenting scale and secure attachment to the father scale. The Pearson correlation test results showed that authoritative parenting was positively related to secure attachment to father. The analysis proved that authoritative parenting was significantly related to adolescents’ attachment to their fathers Copyright © 2020. Psikoislamika: Jurnal Psikologi dan Psikologi Islam